IL-10/STAT5 axis suppresses miR-140 to upregulate B7-H4 expression in RAW264.7 cells - Dandan Zhu; Guo Chen; Guo Chen; Pei Shen; Weiliang Fan; Chuxin Ji; Yinong Duan; Wenxi Gao; Wenxi Gao (Frontiers in Cellular and Infection Microbiology)
IntroductionSchistosomiasis japonica, a zoonotic parasitic disease, induces complex immune regulation during infection. The inflammatory responses and immunosuppressive mechanisms co-exist to maintain immune homeostasis in schistosomiasis. B7-H4 is a critical immune checkpoint molecule that modulates T cell activation and exerts immunosuppressive effects. Our previous investigations revealed that B7-H4 mRNA expression was elevated in mice infected with Schistosoma japonicum, with interleukin-10 (IL-10) demonstrating regulatory capacity to enhance B7-H4 expression in RAW264.7 macrophages. In this study, we further explore the mechanism underlying IL-10-mediated B7-H4 upregulation.MethodsWestern blot was performed to detect B7-H4 expression levels, both in mice infected with Schistosoma japonicum and in RAW264.7 cells stimulated with IL-10. RT-qPCR was performed to screen microRNAs (miR-140 et al.) in RAW264.7 cells stimulated with IL-10. Then dual-luciferase reporter assay was performed to confirm that miR-140 can directly bind to the 3’UTR of B7-H4. miR-140 promoter activity in RAW264.7 cells was also detected via dual-luciferase reporter assays. In addition, ChIP was performed to confirm the binding of transcription factors and miR-140 promoter.ResultsNotably, miR-140 was decreased in IL-10-treated microphages, accompanied by B7-H4 expression was upregulated. miR-140 can directly bind to the 3’UTR of B7-H4 and then inhibit the expression of B7-H4 in RAW264.7 cells. Meanwhile, miR-140 mimics can also attenuate IL-10-induced B7-H4 expression in RAW264.7 cells. Then we found that IL-10 may inhibit miR-140 promoter activity in RAW264.7 cells through transcription factors that binding to the - 576/- 94 bp region of the miR-140 promoter. Results by Western blot and ChIP further indicated that IL-10 could downregulate miR-140 promoter activity in a STAT5 dependence manner. After the sequence of STAT5 binding site within the - 456/- 446 bp region of the miR-140 promoter was mutated, IL-10 failed to suppress the activity produced by mutant miR-140 promoter.DiscussionIn summary, IL-10 can inhibit miR-140 through STAT5, thereby upregulating the expression of B7-H4 in RAW264.7 cells. This study may suggest a new mechanism underlying IL-10-mediated B7-H4 upregulation in macrophages.